Adaptations to Postural Perturbations in Patients With Freezing of Gait - Bekkers, Esther M. J.; Van Rossom, Sam; Heremans, Elke; Dockx, Kim; Devan, Surendar; Verschueren, Sabine M. P.; Nieuwboer, Alice (Frontiers in Neurology, 2018)
Introduction: Freezing of gait (FOG) is a powerful determinant of falls in Parkinson’s disease (PD). Automatic postural reactions serve as a protective strategy to prevent falling after perturbations. However, differences in automatic postural reactions between patients with and without FOG in response to perturbation are at present unclear. Therefore, the present study aimed to compare the response patterns and neuromuscular control between PD patients with and without FOG and healthy controls (HCs) after postural perturbations. Methods: 28 PD patients (15 FOG+, 13 FOG-) and 22 HCs were included. Participants stood on a moveable platform while random perturbations were imposed. The first anterior platform translation was retained for analysis. Center of pressure (CoP) and center of mass (CoM) trajectories and trunk, knee and ankle angles were compared between the three groups using the Statistical Parametric Mapping technique, allowing to capture changes in time. In addition, muscle activation of lower leg muscles was measured using EMG. Results: At baseline, FOG+ stood with more trunk flexion than HCs (p=0.005), a result not found in FOG-. Following a perturbation, FOG+ reacted with increased trunk extension (p=0.004) in comparison to HCs, a pattern not observed in FOG-. The CoM showed greater backward displacement in FOG- and FOG+ (p=0.008, p=0.027). Both FOG+ and FOG- showed increased co-activation of agonist and antagonist muscles compared to HCs (p=0.010), with no differences between FOG+ and FOG-. Conclusions: Automatic postural reactions after a sudden perturbation are similar between PD subgroups with and without FOG but different from HCs. Reactive postural control, largely regulated by brain stem centers, seems to be modulated by different mechanisms than those governing freezing of gait. Greater differences in initial stance position, enhanced by joint stiffening, could however underlie maladaptive postural responses and increase susceptibility for balance loss in FOG+ compared to FOG-.